1993
DOI: 10.1111/j.1600-0447.1993.tb03410.x
|View full text |Cite
|
Sign up to set email alerts
|

The lifetime prevalence of anxiety disorders in Iceland as estimated by the US National Institute of Mental Health Diagnostic Interview Schedule

Abstract: The lifetime prevalence of anxiety disorders was estimated in a study of the prevalence of mental disorders in Iceland. The survey instrument was an Icelandic translation of the US National Institute of Mental Health Diagnostic Interview Schedule. The cohort consisted of one half of those born in the year 1931. The participation rate was 79.3%. The overall prevalence of anxiety disorders was 44%, with phobia effecting 18%. The most common anxiety disorder was generalized anxiety, which had a prevalence of 22% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 14 publications
5
29
0
1
Order By: Relevance
“…Age interacted with sex, with males showing higher exposure with age but no systematic age-related PTSD; female exposure did not shift with age, yet lifetime PTSD was lowest in the oldest group (8.9%), suggesting cohort factors that implicate beliefs. A significant Icelandic study using similar criteria found all PTSD cases were female, with 1.3% affected (19); the contrasting US-Icelandic rates suggest cultural factors.…”
Section: Beliefs and Cognitive Distortionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age interacted with sex, with males showing higher exposure with age but no systematic age-related PTSD; female exposure did not shift with age, yet lifetime PTSD was lowest in the oldest group (8.9%), suggesting cohort factors that implicate beliefs. A significant Icelandic study using similar criteria found all PTSD cases were female, with 1.3% affected (19); the contrasting US-Icelandic rates suggest cultural factors.…”
Section: Beliefs and Cognitive Distortionsmentioning
confidence: 99%
“…The lifetime prevalence ofPTSD is quite low in the general US population, with 5% of men and 10% of women meeting the criteria (13); in Iceland, the rate in a more inclusive sample was only 0.6% (19).…”
Section: Prevalence Of Toxic Life Events and Posttraumatic Disordermentioning
confidence: 99%
“…Although this premise is now widely accepted in adults, [1][2][3][4][5] supporting data in children and adolescents have accumulated more gradually. 6 -12 Several studies of adolescents have found lifetime prevalence rates for OCD 6 -12 ranging from 1.9% to 4.1% with reported rates of subclinical symptoms as high as 19%.…”
mentioning
confidence: 99%
“…An inexperienced instructor might easily overestimate the abilities of a novice person. Such an overestimation could lead to a near-drowning accident with a significant impact on the mental status of the participant since it could lead to aquaphobia, a type of anxiety disorder (Lindal and Stefansson 1993).…”
Section: Discussionmentioning
confidence: 99%